Stock Market Reaction to Indonesia Presidential and Legislative Election - Erna Listyaningsih; Eka Sariningsih; Ritali Mudrikah (Bina Nusantara University, 2020)
The research investigated the reaction to Jakarta Islamic Index (JII) stocks around the Indonesia Presidential and Legislative Election in 2019. It was the first time that the election of the president and legislative assembly was held on the same day in Indonesia. The sample used was 30 stocks of JII. The event study methodology was conducted on this issue. The results show a significant positive abnormal return on the tenth day before the event and the seventh day after the event. From the liquidity, it is found that this event has a strong effect on Trading Volume Activity (TVA) of JII stocks surrounding the event. Additionally, another liquidity proxy, namely bid-ask spread, has the same result by experiencing a significant positive difference before and after the event. These results indicate that the information on the event is sufficient to influence the price, TVA, and size of the bid-ask spread of JII stock.